al-Riwāyāt al-mufīdah fī ʿilm al-trājīda - Racine, Jean, 1639-1699
[Three tragedies by Racine, namely, "Esther," "Iphigénie," and "Alexandre le Grand," translated into vernacular Arabic verse by Muḥammad ʿUthmān Jalāl. To which is appended a brief sketch of the history of Egypt from the accession of Muḥammad ʿAlī Pasha, composed in verse by the translator].